Adoption and use of a semi-gasifier cooking and water heating stove and fuel intervention in the Tibetan Plateau, China. (29th June 2017) - Clark, S; Carter, E; Shan, M; Ni, K; Niu, H; Tseng, J T W; Pattanayak, S K; Jeuland, M; Schauer, J J; Ezzati, M; Wiedinmyer, C; Yang, X; et al.
Abstract: Improved cookstoves and fuels, such as advanced gasifier stoves, carry the promise of improving health outcomes, preserving local environments, and reducing climate-forcing air pollutants. However, low adoption and use of these stoves in many settings has limited their benefits. We aimed to improve the understanding of improved stove use by describing the patterns and predictors of adoption of a semi-gasifier stove and processed biomass fuel intervention in southwestern China. Of 113 intervention homes interviewed, 79% of homes tried the stove, and the majority of these (92%) continued using it 5–10 months later. One to five months after intervention, the average proportion of days that the semi-gasifier stove was in use was modest (40.4% [95% CI 34.3–46.6]), and further declined over 13 months. Homes that received the stove in the first batch used it more frequently (67.2% [95% CI 42.1−92.3] days in use) than homes that received it in the second batch (29.3% [95% CI 13.8−44.5] days in use), likely because of stove quality and user training. Household stove use was positively associated with reported cooking needs and negatively associated with age of the main cook, household socioeconomic status, and the availability of substitute cleaner-burning stoves. Our results show that even a carefully engineered, multi-purpose semi-gasifier stove and fuel intervention contributed modestly to overall household energy use in rural China.